The neuroprotective effect of erythropoietin in docetaxel-induced peripheral neuropathy causes no reduction of antitumor activity in 13762 adenocarcinoma-bearing rats. - Cervellini, I; Bello, E; Frapolli, R; Porretta-Serapiglia, C; Oggioni, N; Canta, A; Lombardi, R; Camozzi, F; Roglio, I; Melcangi, R; D'incalci, M; Lauria, G; et al. (2010)
Taxanes, including docetaxel (DOCE), are severely neurotoxic, causing disabling peripheral neuropathy. Co-treatment with neuroprotective agents has been proposed to prevent or reverse this. Besides its hemopoietic effects, erythropoietin (EPO) has neuroprotective and neurotrophic properties and when administered systemically it has a wide range of neuroprotective action in animal models of nervous system damage, including cisplatin-induced peripheral neurotoxicity. The present study investigated the effects of EPO on chemotherapy-induced peripheral neurotoxicity (CINP) by DOCE in vivo and whether it interfered with tumor growth or antitumor activity. Female Fischer rats bearing 13762 mammary carcinoma were randomly divided into four groups: untreated, treated with EPO, DOCE, or DOCE + EPO. DOCE was given once a week (5 mg/kg, i.v.) and EPO three times a week (50 microg/kg i.p.), for 4 weeks. Three other groups of rats without tumors were left untreated or given DOCE or DOCE + EPO. The rats were observed for 4 weeks after treatment. CINP and neuroprotection were evaluated by measuring nociception, electrophysiological, and biochemical parameters. EPO protected against CINP, and tumor growth in EPO-treated rats was the same as in controls. EPO significantly improved the thermal threshold, tail nerve conduction velocity, and intra-epidermal nerve fiber density. These benefits lasted through the follow-up period and EPO speeded-up spontaneous recovery after treatment withdrawal. EPO did not impair DOCE antitumor activity. Since CINP induced by DOCE reproduces the clinical utility of taxane in humans, the findings reported might provide a basis for investigating EPO as a neuroprotective agent in patients receiving therapy with DOCE.